The role of health in households’ balancing act for lifestyles compatible with the Paris agreement: qualitative results from Mannheim, Germany - Herrmann, Alina; Sauerborn, Rainer; Nilsson, Maria (International journal of environmental research and public health, 2020)
Household lifestyles are the main drivers of climate change. Climate change mitigation measures directed to households often have substantial health co-benefits. The European mixed-methods study HOPE (HOuseholds' Preferences for reducing greenhouse gas emissions in four European high-income countries) investigates households’ preferences for reducing greenhouse gas emissions and particularly researches the role of information on health co-benefits in household' decision making. The results presented in this study are derived from 18 qualitative interviews, conducted with a subsample of households from Mannheim, Germany. The in-depth interviews were transcribed verbatim, analyzed with a qualitative content analysis, supported by NVivo software. They showed that, in order to reduce their greenhouse gas emission in a way compatible with the 1.5°C goal, households have to undertake a difficult balancing act, considering factors from the individual sphere, such as health co-benefits, as well as from the public sphere, such as (climate) policies. Shared responsibility and equity are important aspects of households. In conclusion, health is an important factor in households' decision making. However, information policies about health co-benefits need to go along with structural policy measures, in order to support households effectively in the implementation of healthy and climate-friendly lifestyles, especially in sectors where behavior change is difficult, like the mobility sector.
Gesehen am 26.03.2020